Early Enteral Nutrition and Short-Term Laboratory Dynamics in Acute Stroke With Dysphagia: Hemorheology, Inflammatory Cytokines, and Intestinal Barrier Biomarkers: Enteral Nutrition, Stroke & Dysphagia: Microcirculation and Cytokines - Wang, Yanping; Wang, Yuan (Journal of Medical Biochemistry, 2026)
Background:To examine whether enteral nutrition support modulates blood microcirculation, stress-related cytokines, and nutrition/metabolism biochemical indices in patients with acute cerebral stroke (CS) complicated by swallowing disorders (SD), and to explore possible biochemical links among these changes.Methods:This retrospective cohort study included 126 patients with acute CS complicated by SD admitted to our hospital from August 2022 to August 2025. According to the intervention plan, patients were assigned to an observation group (68 cases; enteral nutrition support) or a control group (58 cases; routine fluid replacement therapy). Fasting venous blood was collected before intervention (T0), at 7 days (T1), and at 14 days (T2). Hemorheological parameters and red blood cell functional indices were measured with an automatic hemorheology analyzer; stress cytokines, inflammatory mediators, and intestinal barrier–related indicators were quantified by enzyme-linked immunosorbent assay; nutrition metabolism–related indices were determined using an automatic biochemical analyzer.Results:In the observation group, hemorheological parameters improved progressively after intervention. Compared with T0, whole-blood high-shear viscosity (W-Vis-H), whole-blood low-shear viscosity (W-Vis-L), and fibrinogen were lower at T1 and further reduced at T2, while the red blood cell deformation index (RDI) increased (P
Keywords: Acute stroke; Dysphagia; Enteral nutrition support; Blood microcirculation; Stress cytokines; Nutritional metabolism